Cambios en lengua y glándulas salivales por efecto de la metformina en Rattus rattus var. albinus. - Lema Carrera, Mayra Alexandra (Universidad Nacional de Chimborazo,2017, 2017)
The aim of the present study was to identify the effect of metformin on the tongue and salivary glands (parotid gland) of Rattus rattus var. Albinus. For this, the histological sections observed in both the Hematoxylin - Eosin and the T. de Gomori staining of the Rattus rattus were studied. They were submitted to an experimental study and were separated in the control group, which were administered via a gastric probe 3 volumes % Body weight of physiological saline (SSF) for 14 days and a problem group that was administered via gastric probe 3% volume of body weight concentrations of 500mg / kg metformin dissolved in physiological saline (SSF) for 7 Days and later the dose of metformin 750 mg / kg was increased during the remaining 7 days. The results show that by comparing histological sections of tongue and parotid gland Rattus rattus var. Albinus treated with metformin and in comparison to the control group, we found the tissues of the tongue and salivary glands (G. parótida) without presence of alterations, but this does not mean that alterations can be present in other oral tissues. El objetivo del presente fue identificar el efecto de la metformina en lengua y glándulas salivales (glándula parótida) de Rattus rattus var. albinus. Para esto se han comparado los cortes histológicos observados tanto en la con tinción Hematoxilina – Eosina y T. de Gomori de las Rattus rattus que fueron sometidas a un estudio experimental siendo separadas en grupo control que se les administró vía sonda oro gástrica un volumen del 3% del peso corporal de solución salina fisiológica (SSF) por 14 días y un grupo problema que fue administrado vía sonda oro gástrica un volumen del 3% del peso corporal de concentraciones de 500mg/kg metformina disuelta en solución salina fisiológica (SSF) por 7 días y posterior se le aumento la dosis de la metformina 750mg/kg durante los 7 días restantes. Los resultados muestran que mediante la comparación de los cortes histológicos de lengua y glándula parótida Rattus rattus var. albinus sometido ...